"Habt ihr was für mich?": Critical Collectivity in Terézia Mora's "Selbstbildnis mit Geschirrtuch" (2016). (30th August 2021) - Lien, Duncan Gullick
Abstract : Among literary responses to contemporary migration to Germany, Terézia Mora's short story "Selbstbildnis mit Geschirrtuch" stands out as a critical engagement with the various forms of exclusion migrants face. The story recasts the Holocaust‐era refugee experience of the German‐Jewish painters Felka Platek and Felix Nussbaum in contemporary Germany. Although others have considered the relation of Holocaust memory to migration, Mora approaches it from a novel perspective informed by Walter Benjamin's notion of weak messianism and Jean‐Luc Nancy's philosophy of negative community. Motifs of infernal descent are found throughout the story and dramatize the protagonist's exclusion. Weak messianism and negative community shape the response to exclusion in the narrative. Specifically, the story dramatizes alternative forms of being together beyond linguistic borders. Accordingly, this paper demonstrates how the text interrupts the temporal, physical, and linguistic borders of German society, gesturing towards the possibility of collectivity not underwritten by exclusion of the other.